Money matters content analysis of business reporting in TV Patrol and 24 Oras Katrina T. Mina ; Lucia Tangi, adviser. - Mina, Katrina T. 1998- (2018)
"The objective of the study is to measure the importance given to business, economic and financial reporting in primetime newscasts 24 Oras and TV Patrol. The research analyzed two newscasts each month for a total of 48 newscasts from October 2016 to September 2018 with the use of content analysis. Furthermore, the research also interviewed editors from both broadcasts and an expert on business, economic, and financial reporting. The study concluded that even though business and economic new packages are one of the most frequent kinds of news packages aired, the discrepancy of its number from other types of news such as crime and political news is still substantial. Furthermore, topics such as exchange rate, labor, transportation and basic commodities appear the most frequent because they are perceived to be the concerns of the audience. The research also concluded that even though the news packages about business and economics have good hooks because of case studies, they still lack on proper contextualization and development in order to explain the issue better."